Neuro-nutraceutical potential of Asparagus racemosus: A review - Majumdar S.; Gupta S.; Prajapati S.K.; Krishnamurthy S. (My University, 2025)
Debilitating neuropsychiatric and neurodegenerative conditions are associated with complex multifactorial pathophysiology. Their treatment strategies often only provide symptomatic relief, delaying disease progression without giving a complete cure. Potent and safer treatment alternatives beyond symptomatic relief are sought. Herbal supplements have surely been explored due to their multiple component nature to enhance the effect of western medications. One such well-documented nutraceutical in the ancient Greek, Chinese, and Ayurvedic medicine system known for its various medicinal benefits is Asparagus racemosus. Widely used for its lactogenic properties, A. racemosus is also cited in Ayurveda as a nervine tonic. A. racemosus based nutraceuticals have shown to possess adaptogenic, neuroprotective, antioxidant, anti-inflammatory, and nootropic activity under preclinical and clinical settings without posing significant adverse effects. A. racemosus extracts restore the perturbed neurotransmitters and prevent oxidative neuronal damage. From the available neuropharmacological researches, the physiological actions of A. racemosus can ultimately be directed for either augmentation of cognitive ability or in the management of neurological conditions such as stress, anxiety, depression, epilepsy, Parkinson's, and Alzheimer's disease. The studies focus on the multi-component extract, and the lack of standardization has been a major hurdle in preventing the allotment of reported neuropharmacological activity to one of the phytoconstituent. Herbal standardization of the plant extract based on a specific biomarker can help elucidate the intricate biomolecular pathway and neurocircuitries being involved. This, followed by rigorous standardized clinical trials, fixing dosages, and determining contraindications would facilitate the translation of A. racemosus to a FDA-approved neuromedicine for neurological disorders. © 2021